A concept analysis of compassionate midwifery. (5th December 2016) - Ménage, Diane; Bailey, Elizabeth; Lees, Susan; Coad, Jane
Abstract: Aim: To report a concept analysis of compassionate midwifery. Background: Recently, compassion has been incorporated into United Kingdom nursing and midwifery language through strategy, policy, recruitment and education. Professional standards direct midwives to practise compassionately therefore the concept of compassionate midwifery exists, although this has yet to be explored as a concept in the UK or internationally. An understanding of what constitutes compassionate midwifery has the potential to increase midwifery knowledge and improve practice. Design: Concept Analysis. Data sources: Literature from 1990–2015 was searched using MEDLINE, CINAHL, PsycINFO and ETHOS. Grey literature and examples of everyday usage of the concept were searched using Google. Methods: An adapted model of evolutionary concept analysis. Results: Explanations of compassionate midwifery were absent in the literature therefore the gathered data were evaluated in relation to elements of the compassion process: recognition of suffering, emotion, motivation and action. Compassionate midwifery is defined as the interrelations of authentic presence, noticing suffering, empathy, connectedness/relationship, emotion work, motivation to help/support, empowering women and alleviating suffering through negotiation, knowledge and skills. Antecedents and consequences were also identified and depicted in a schematic representation of the concept. Conclusion: This concept analysis provides a unique examination of compassionate midwifery and starting point for reflection on practice, education and further analysis. Empirical studies will provide the potential to take the process further by studying the experience of compassionate midwifery from different perspectives. A theory of compassionate midwifery will develop as new findings emerge.